KEDUDUKAN SYARIAT ISLAM DALAM TATA NEGARA INDONESIA - Ali Abubakar (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2014)
The implementation of Sharia in Aceh was based on a people view of life in Aceh who believes their existence cannot be separated from the Allah guidance. In fact, Islamic Sharia is already implemented in Aceh since the Kingdom of Aceh Darussalam, as evidenced by the presence of various manuscripts focusing on Islam. Legally, it is recognized in Indonesia in Article 29 UUD 1945 as wells as in the Central Government through Act No. 44 of 1999 and Act 11 of 2006. Academically, although the imposition of Sharia in Aceh is based on civil law, but it cannot be denied that in the application process of common law also plays an important role. Kata Kunci: Syariat Islam, wewenang, qanun, lex spesialis, agama, jinayat, civil law, common law.